Why Special Economic Zones? Using Trade Policy to Discriminate across Importers - Grant, Matthew (American Economic Review, 2020)
Tariffs are generally assumed to depend on the product, not the identity of the importer. However, special economic zones are a common, economically important policy used worldwide to lower tariffs on selected goods for selected manufacturers. I show this is motivated by policymakers’ desire to discriminate across buyers when a tax is intended to raise prices for sellers, through a mechanism distinct from existing theories of optimal taxation. Using a new dataset compiled from public records and exogenous changes in imports of intermediate goods, I find the form, composition, and size of US zones are consistent with the theory. (JEL F13, F14, L60, R32)